2011
DOI: 10.1186/1297-9716-42-92
|View full text |Cite
|
Sign up to set email alerts
|

Skin mucus of Cyprinus carpio inhibits cyprinid herpesvirus 3 binding to epidermal cells

Abstract: Cyprinid herpesvirus 3 (CyHV-3) is the aetiological agent of a mortal and highly contagious disease in common and koi carp. The skin is the major portal of entry of CyHV-3 in carp after immersion in water containing the virus. In the present study, we used in vivo bioluminescence imaging to investigate the effect of skin mucus removal and skin epidermis lesion on CyHV-3 entry. Physical treatments inducing removal of the mucus up to complete erosion of the epidermis were applied on a defined area of carp skin j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 20 publications
3
100
1
Order By: Relevance
“…The composition and rate of mucus secretion has been observed to change in response to microbial exposure or to environmental fluctuations (Ellis, 2001). Raj et al (2011) reported that skin mucus removal and epidermal lesions in Cyprinus carpio in invitro experiments enhanced the entry of CyHV-3 virus while the presence of skin mucus of Cyprinus carpio conferred protection against the entry of the virus. Numerous studies on innate immunity in fish have shown that fish epidermal mucus can inhibit the growth of some bacteria and therefore may have a potential source of novel antimicrobial components in it (Wei, Xavier, & Marimuthu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The composition and rate of mucus secretion has been observed to change in response to microbial exposure or to environmental fluctuations (Ellis, 2001). Raj et al (2011) reported that skin mucus removal and epidermal lesions in Cyprinus carpio in invitro experiments enhanced the entry of CyHV-3 virus while the presence of skin mucus of Cyprinus carpio conferred protection against the entry of the virus. Numerous studies on innate immunity in fish have shown that fish epidermal mucus can inhibit the growth of some bacteria and therefore may have a potential source of novel antimicrobial components in it (Wei, Xavier, & Marimuthu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, mucus plays a critical role in the defence mechanism of the fishes by also acting as a biological barrier [79][80][81]. Skin mucus has evolved to have robust mechanisms that can trap and immobilize pathogens before they can contact epithelial surfaces, because it is impermeant to most bacteria and many pathogens [82].…”
Section: The Cutaneous Mucus Layermentioning
confidence: 99%
“…The resin embedding technique has also been applied to study ultrastructural aspects of herpesvirus into cells infected by CyHV-3 [17,25,26,27,28], of the Koi herpesvirus (KHV) infecting carp (Cyprinus carpio) [29] and of the CCV (channel catfish virus) in a kind of catfish (Ictalurus nebulosus). 4 From this technique herpesvirus particles were visualized in all stages of development in the nucleus, granular bodies containing virus particles, lamellar structures and altered nuclear membrane, and numerous viral particles in the cytoplasm [24].…”
Section: Discussionmentioning
confidence: 99%